Na batida do Brega Funk: as batalhas de passinho em João Pessoa/PB - Matias, Milena da Costa (2021)
This dissertation addresses the passinho battles that happened in the city of João Pessoa-PB in the period of 2019 and 2020. The passinho battles emerged after the rise of Brega Funk, a rhythm from Pernambuco. To observe this youth practice, I chose two battles: the Batalha de Mangabeira 7 and the Batalha do Busto. I used participant observation and analysis of the speeches of the young people who attend the battles. I dialogued face-to-face and online due to the Covid-19 pandemic and observed the use of media and social networks by young people who consume Brega Funk. The guiding theoretical discussion was based on studies of urban anthropology (Magnani, 2005), (Velho, 1978), youth cultures (Souza, 2007), (Pereira, 2017), music (Fontanella, 2005), (Vianna, 1987) and communication (Janotti, 2011), and (Soares, 2017). The results reveal that from the battles young people create sociability networks, music and dance are shown as important pillars in juvenile sociability, and that the passinho battles have become a moment of leisure. They also point out that, through the battles, young people give new meaning to city spaces that are used by other groups with generational, class and economic differences. Based on their musical preference, young people mold themselves to common styles and consumption, create an aesthetic guided by the consumption of music, and give visibility to their creativity around this musical genre, which also reverberates in popularity on social networks. The occupation of these city spaces also shows discourses of disapproval and criminalization of the practices of passinho and the subjects that participate, however, young people have potentiated their talents and creativity through dance and occupied physical and virtual spaces through Brega Funk.